Tinjauan Fikih atas Transfusi Darah dalam Medis Modern - Susanti, Vera; Nasikhah, Umi (Shar-E : Jurnal Kajian Ekonomi Hukum Syariah, 2025)
Blood transfusion is a vital medical practice that saves lives and has become a standard procedure in modern healthcare. Within the Islamic context, it raises fiqhi discussions regarding its permissibility, especially considering that blood is categorized as impure. However, contemporary scholars view transfusion as a necessary act allowed in emergencies to preserve life, aligning with the objectives of Islamic law (maqāṣid al-syarī‘ah). Fatwas issued by religious authorities such as the Indonesian Ulema Council (MUI) and Al-Azhar affirm its permissibility, provided the intention is sincere, medical safety is ensured, and the need is evident. Therefore, blood transfusion is not only medically valid but also religiously endorsed as a form of social worship and humanitarian rescue. This indicates that Islam is a religion that is responsive to human needs.